2015
DOI: 10.1016/j.smr.2014.10.006
|View full text |Cite
|
Sign up to set email alerts
|

The exclusiveness of group identity in celebrations of team success

Abstract: openAccessArticle: Falsecover date: 2015-08-01pii: S1441-3523(14)00089-8Harvest Date: 2016-01-06 13:07:37issueName:Page Range: 396-396href scidir: http://www.sciencedirect.com/science/article/pii/S1441352314000898pubType

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 40 publications
3
34
0
3
Order By: Relevance
“…This contributes knowledge concerning how new organisations can adopt a relationship marketing approach and encourage co-creation from fans (Kim & Trail, 2011). The Owning Our Identity theme also revealed how some individuals considered the role of the community important to their sustained identification, consistent with other research showing the importance of external groups on team identification (Delia, 2015;Heere & James, 2007;Heere, Walker, et al, 2011;McDonald et al, 2015). Consequently, we extend new team research that has shown regional identification impacts team identification (Harada & Matsuoka, 1999;Lock et al, 2011) by demonstrating how team identification can affect integration within the representative city.…”
Section: Identification With New Sport Teamssupporting
confidence: 81%
See 2 more Smart Citations
“…This contributes knowledge concerning how new organisations can adopt a relationship marketing approach and encourage co-creation from fans (Kim & Trail, 2011). The Owning Our Identity theme also revealed how some individuals considered the role of the community important to their sustained identification, consistent with other research showing the importance of external groups on team identification (Delia, 2015;Heere & James, 2007;Heere, Walker, et al, 2011;McDonald et al, 2015). Consequently, we extend new team research that has shown regional identification impacts team identification (Harada & Matsuoka, 1999;Lock et al, 2011) by demonstrating how team identification can affect integration within the representative city.…”
Section: Identification With New Sport Teamssupporting
confidence: 81%
“…Here, we regularly reflected upon and discussed our allocation of concepts to themes with each other and with colleagues who were not involved in the research. This was done to ensure the themes were trustworthy and conceptually sound, and this process is consistent with the standards applied in other recent sport management enquiries (e.g., Delia, 2015;Filo, Cuskelly, & Wicker, 2015). The third step involved condensing the themes so that they were organised into primary and sub-themes, which allowed the major findings, discussed next, to be easily presented.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The propensity of sport consumers to bask in the reflected glory (BIRG) of winning teams provides a salient example of this phenomenon (Cialdini et al, 1976;Delia, 2015;Fink et al, 2002;Fisher & Wakefield, 1998;Trail et al, 2012). However, sport consumers also support unsuccessful teams (Fisher & Wakefield, 1998;Wann & Branscombe, 1990).…”
Section: Superordinate Identificationmentioning
confidence: 99%
“…In a recent qualitative study, Delia (2015) explored how consumers used multiple external group memberships to BIRG or blast. She found that prior to, during, and after matches the complex repertoire of group memberships to which consumers belonged combined into a simpler identity structure.…”
Section: Relations Between Multiple In-group Identitiesmentioning
confidence: 99%